From promises to action: Analyzing global commitments to tackle hunger and food insecurity - Zorbas, Christina; Resnick, Danielle; Jones, Eleanor; Suri, Shoba; Iruhiriye, Elyse; Headey, Derek D.; Martin, Will; Vos, Rob; Menon, Purnima (Elsevier, 2025)
High-level declarations and commitment statements are a common output of global, intergovernmental meetings and critical to their continued public legitimacy. Yet, to what extent have such statements served as roadmaps for concrete action? To address this question, this paper focuses on commitments to Sustainable Development Goal (SDG) 2, which aims to end hunger, achieve food security, and promote sustainable agriculture by 2030. Using a structured framework with seven domains, we analyzed 148 intergovernmental commitment documents emerging from 78 global meetings focused on SDG2 and organized by ten different global bodies between 2015 and 2023.